(untitled) (Scientific journal of the Fergana State University, 2024)
The article reveals the origins of the modern Uzbek dwelling. In particular, parallels are drawn with the guest room - mehmonkhon, it is noted that building materials such as guval and pakhsa were known in the Middle Ages, as well as burnt bricks. The heating systems of dwellings of the Middle Ages and the present are considered.